(NkOMPLEKSNOE LESOHOZQJSTWENNOE RAJONIROWANIE (B/s - (N{EJNGAUZ(B, (Na(B.(Ns(B.s; (NdOROFEEWA(B, (Na(B.(Na(B.s; (NaKADEMIQ NAUK sssr(B.s (NdALXNEWOSTO^NYJ NAU^NYJ CENTRs ((NwLADIWOSTOK (B:s (NdALXNEWOSTO^NOE KN(B. (NIZD(B-(NWO(B,s, 1980)
(NzAKL(B.: (NS(B. 132-133s
(NlIT(B.: (NS(B. 133-141s
Keywords: (NlESOHOZQJSTWENNOE RAJNIROWANIEs